Pengaruh Jenis Kayu dalam Perendaman Minyak Jelantah dan Plastik LDPE terhadap Stabilisasi Dimensi dan Sifat Mekanik Kayu - Wisnu Wardana; Hastanto Bowo Woesono; Didik Surya Hadi (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2026)
This study aims to determine the effect of wood type and immersion time in plastic solution on the dimensional stability and mechanical properties of wood. This study used a completely randomized design with factorial experiments. The factors used consisted of 2 factors including wood type consisting of three types of wood: sengon, teak, bangkirai, and immersion time factors including three levels, namely: control (0), 20, and 30 minutes, each of which was repeated three times. The parameters observed included the dimensional change ratio (T/R), MOE, MOR, and compressive strength parallel to the grain. The test results for each parameter were analyzed using Analysis of Variance, and if there were significant differences, further testing was carried out using the Tukey test. The results showed that immersion increased the dimensional stability of wood as indicated by a decrease in the T/R ratio in sengon from 1.56 to 1.49 and teak from 1.64 to 1.58, while bangkirai had a higher value of 2.03–2.26. Tukey's test showed that the MOE values ​​differed significantly between wood species, namely sengon 1,239.17 kg/cm², teak 2,715.29 kg/cm², and bangkirai 4,669.53 kg/cm². The MOR values ​​were 571.34 kg/cm², 1,394.91 kg/cm², and 2,182.14 kg/cm², respectively. However, the immersion and the interaction between the two did not differ significantly. The compressive strength parallel to the grain also differed significantly between wood species: sengon (255.34 kg/cm²), teak (435.25 kg/cm²), and bangkirai (752.66 kg/cm²). The immersion treatments differed significantly from the control, but no significant differences were observed between the immersion treatments. The average compressive strength parallel to the wood grain increased with each immersion treatment, from 406.56 kg/cm² (0 min) to 514.07 kg/cm² (20 min) and 522.62 kg/cm² (30 min), without any interaction between the two factors.